Homosexuality as Practice and the Social Implications of Representation. Issue 4 (2nd October 2018) - Ariza, Saúl
ABSTRACT: What tends to be represented when talking about homosexuals is not the diversity of people who have sex with others of the same sex-gender, but a kind of group or a defined collective with some identifiable characteristics and specific identities: a collection of others, a historically oppressed minority, a community. As a result, not all people who practice homosexuality are included in the representations of homosexuals, nor do all included in these conform to the images projected onto them. This involves a series of social and political consequences, related to the reproduction of hegemonic gender and power structures. Therefore, I question the use of these representations in social sciences and propose to consider, as the analysis element, sexual practices and not the identities and categorizations created around them, showing the power relations that exist between them.